TRANSLATION STRATEGIES IN AN ANNOTATED TRANSLATION OF NOVEL SEE ME BY NICHOLAS SPARK - Ariza Purnawati (Asosiasi Dosen Muda Indonesia, 2022)
This research is about an annotated translation which belongs to the area of translation with commentary. The problems of this research are: (1) the difficulties encountered by the researcher (as a translator) during the process of translation, and (2) the difficulties solved during the process of translation. The purposes of this research are: (1) to attain factual information concerning the problems faced by the researcher (as a translator) in translating the source text, and (2) to find out the plausible solutions of those difficulties referring to the principles of translation, the translation strategies, the theories of translation and the theories of both Indonesian and English languages. Introspective and retrospective are used as the methods of the research. The result of this research showed that from the 223 data collected, the researcher purposefully has chosen 25 data to be analyzed. The results of the analysis revealed that out of 223 data, the 25 analyzed data are literal (2 data), loan (2 data), calque (2 data), paraphrase: idiom (2 data) and phrasal verb (2 data), cohesion change (1 datum), unit shift (2 data), distribution change: expansion (2 data) and compression (2 data), explicitness change: implicit-explicit (2 data), transposition (2 data), cultural filtering: naturalization (1 datum) and adaptation (1 datum), and information change (2 data). The finding of this research is that not all of the thirty translation strategies and the six principles of translation are employed because there are only twenty-five data analyzed.